2021
DOI: 10.1088/1674-1137/abcf22
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrum and strong decays of strangeonium in a constituent quark model *

Abstract: In this work we calculate the mass spectrum of strangeonium up to the multiplet within a nonrelativistic linear potential quark model. Furthermore, using the obtained wave functions, we also evaluate the strong decays of the strangeonium states with the model. Based on our successful explanations of the well established states … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 114 publications
3
17
0
Order By: Relevance
“…The f 0 (1370) is assigned to be the 1 3 P 0 ss state by a recently quark model study of ss meson mass spectrum [6], which is consistent with quark model mass spectrum studies [3][4][5] but conflict with the experimental conclusion that the f 0 (1370) decays mostly into pions. Actually, since the average mass of the f 0 (1370) is from 1200 MeV to 1500 MeV [23], the broad f 0 (1370) resonance may correspond to two different states, each with the nn or ss content.…”
Section: A J = 0 Statessupporting
confidence: 55%
See 2 more Smart Citations
“…The f 0 (1370) is assigned to be the 1 3 P 0 ss state by a recently quark model study of ss meson mass spectrum [6], which is consistent with quark model mass spectrum studies [3][4][5] but conflict with the experimental conclusion that the f 0 (1370) decays mostly into pions. Actually, since the average mass of the f 0 (1370) is from 1200 MeV to 1500 MeV [23], the broad f 0 (1370) resonance may correspond to two different states, each with the nn or ss content.…”
Section: A J = 0 Statessupporting
confidence: 55%
“…However, the 1 3 P 0 state is always the lightest state in the three 1 3 P J states (J = 0, 1, 2) in potential model studies [2][3][4][5][6], which is confirmed in the observation of the χ cJ (1P ) and χ bJ (1P ) for charmonium and bottomonium mesons respectively. Since the mass splitting between χ c0 (1P ) and χ c2 (1P ) is around 150 MeV, and the mass splitting between χ b0 (1P ) and χ b2 (1P ) is around 50 MeV [23], one may conclude that the 1 3 P 0 nn and ss states should be obviously lighter than 1 3 P 2 nn and ss states which are widely accepted as the f 2 (1270) and f 2 (1525) respectively [8].…”
Section: A J = 0 Statesmentioning
confidence: 56%
See 1 more Smart Citation
“…It should be mentioned that we cannot obtained stable solutions for some states due to the singular behavior of 1/r 3 in the spin-dependent potentials. To overcome the singular behavior, following the method of our previous works [121][122][123][124][125], we introduce a cutoff distance r c in the calculation. Within a small range r ∈ (0, r c ), we let 1/r 3 = 1/r 3 c .…”
Section: Parametersmentioning
confidence: 99%
“…Yet, the φ(2170) resonance is not taken into account in the present work, 1 since the experimental information of it is still diverse, and the measured mass and width of φ(2170) resonance are controversial [27][28][29][30][31][32][33][34][35]. Indeed, there have also been different theoretical explanations for φ(2170) resonance [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%